Dilema Arab Pegon di Era Modern - Soleha, Zachro; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
This study describes the changes and dilemmas faced by the Pegon script, a traditional Javanese writing system, in facing the modern era. The main focus of this research is on the transformation of the Pegon script, its use, maintenance, and impact on Javanese cultural heritage. In the method steps, this research carried out identification and selection of literature as well as evaluating the credibility of relevant information sources. An in-depth analysis was carried out on changes in the Pegon script, both from a linguistic and aesthetic perspective, taking into account the influence of technology and modernization. This research also highlights the social and cultural impact of using the Pegon script in the modern era. By paying attention to people's attitudes towards these changes, this study aims to provide a holistic picture of the evolution of the Pegon script and its consequences for local cultural identity and heritage. In addition, this research explores the link between changes in the Pegon script and the education sector, considering the implications for the curriculum and cultural preservation efforts. It is hoped that the results of this literature review will provide in-depth insight into the dilemmas faced by the Pegon script in facing the flow of modernization. The conclusions drawn from this study can provide a basis for developing policies, educational strategies, and cultural preservation efforts to maintain the sustainability and relevance of the Pegon script in the context of modern society.